Pengaruh Human Relations Terhadap Motivasi Belajar Masa Pandemi Covid-19 (Studi Kausalitas Kalangan Pelajar SMAN 2 Kota Medan) - Fristanti, Nadya Alifa; Anugrah, Dadan (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
The aim of this research is to determine the effect of human relations activities on student learning motivation during the covid-19 pandemic which was carried out by educational institutions SMAN 2 Kota Medan. The research paradigm used in this research is positivistic with quantitative methods and uses survey research or questionnaires as data collection methods with a number of samples 92 respondents that were determined by the Slovin formula. The data analysis technique used is a simple linear regression analysis technique, the coefficient of determination test, and the T test as a hypothesis test which is processed using SPSS version 26. This research resulted in a regression equation Y = 13.178 + 0.510X with the output of the Anova table obtaining a sig value. 0.000 < 0.05. This means that there is a significant influence between human relations activities on student motivation at SMAN 2 Kota Medan. The value of the coefficient of determination obtained is 0.437 or equal to 43,7%.